2015
DOI: 10.1017/jfm.2015.634
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of rotating-disk boundary-layer flow with surface roughness

Abstract: Rotating-disk boundary-layer flow is known to be locally absolutely unstable at R > 507 as shown by Lingwood (J. Fluid Mech., vol. 299, 1995, pp. 17-33) and, for the clean-disk condition, experimental observations show that the onset of transition is highly reproducible at that Reynolds number. However, experiments also show convectively unstable stationary vortices due to cross-flow instability triggered by unavoidable surface roughness of the disk. We show that if the surface is sufficiently rough, laminar-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 31 publications
4
28
0
Order By: Relevance
“…(6). The distribution matches very well with the experimental data of Imayama et al [21]. xp(αRe), where α is the growth rate.…”
Section: Code Verification By Convectively Unstable Mode Computationsupporting
confidence: 87%
See 2 more Smart Citations
“…(6). The distribution matches very well with the experimental data of Imayama et al [21]. xp(αRe), where α is the growth rate.…”
Section: Code Verification By Convectively Unstable Mode Computationsupporting
confidence: 87%
“…The finding that the wavenumber and the frequency are both 32 indicates that the 32 spiral vortices are stationary with respect to the disk surface, which is consistent with the previously reported experimental results. Both in our computation, in which the flow field was excited by artificial disturbance at an upstream location of Re ~ 255, and the experimental data of Imayama et al [20,21], in which the disturbance was only naturally provided from the disk surface, the velocity fluctuations were stationary with respect to the disk surfaces and their wavenumbers or the number of spiral vortices were similar. It can be judged that the velocity fluctuation in this computation grew by the convective instability as in experiments.…”
Section: Code Verification By Convectively Unstable Mode Computationsupporting
confidence: 65%
See 1 more Smart Citation
“…For r > r end the flow will have entered the nonlinear region and r end thus separates the linear and nonlinear regions. In experiments, Imayama et al (2013) defined the transitional Reynolds number (also including Imayama et al 2012Imayama et al , 2014Imayama et al , 2016 from their power spectra where the first harmonic of the stationary vortices reaches an amplitude of 10 −6 . Using this threshold for the onset of nonlinearity in our simulations, it will be shown that the first harmonics of the travelling disturbances reach the same amplitude in our corresponding spectra at our position r end .…”
Section: Introductionmentioning
confidence: 99%
“…[5]. Slightly later the transition scenario on the disk was further investigated experimentally [6] and via direct numerical simulations [7], and it was conjectured that an absolute secondary instability on top of the primary vortices was likely to be the trigger for transition.…”
mentioning
confidence: 99%